Typology Of Schools In Rural Areas Of Andijan Region (Journal of Pedagogical Inventions and Practices, 2022)
This article provides information about changes in urban planning, not only about the restoration of historical monuments in cities and regions, but also about the construction of a number of modern professional colleges and schools. The typology of schools in rural areas of the Andijan region is also highlighted